Modificación de superficies de silicio mediante moléculas de anclaje nanoparticuladas para ser utilizadas en dispositivos electrónicos modernos - Montero-Villalobos, Mavis; Gutiérrez-Fallas, Dionisio; Vega-Baudrit, José; Urcuyo-Solórzano, Roberto; Sánchez-Zamora, Alejandra; González-Flores, Diego; Salazar-Morera, Norberto (Instituto Tecnológico de Costa Rica, 2011)
Surface modification and attachment of molecules is one of the issues nanotechnology has emerged in recent years. Mainly, it has been noted its potential in the electronics industry. That is why, through the plan of strengthening education company Intel of Costa Rica, the investigation is power in this field in our country, with projections of the possibility that this technology replace technology Silicon was. As a general objective the integration of nanoparticles was raised, known relevance in the field of electronics, in modified surfaces silicon, from anchor molecules. Among the most important specific objectives was proposed: the study of state of the art in synthesizing anchor molecules and the synthesis of nanoparticles. Moreover, within the experimental activities, it was intended obtain the synthesis of materials by the methods considered most suitable. Another important objective was to achieve characterization materials, mainly their structure, microstructure and electrical properties. Two notable objectives were to foster a research relationship between the INTEL and public universities in our country, in addition to promoting the participation of students with the purpose of starting with the formation of a generation of people with skills in the field of nanotechnology. The methodology used in the project was running this in three stages, each with a duration of a period of one year. In the first stage the study of the prior art, in addition to the preliminary synthesis of certain materials within these organic molecules and nanoparticles from a method of electrolysis was performed. As a second step the optimization of the selected methods are planned and anchoring the nanoparticle experimental study on silicon surfaces previously selected. In the third stage we continued with the synthesis of new molecular structures and particularly with the development of skills for the characterization of the materials at different stages. This project is protected under intellectual rights protection of the University of Costa Rica, however, my participation was I associated with different stages, of which mention more results major: a) Developing skills in using various materials characterization techniques associated with XRD (powder diffraction, reflectance). b) Participation in the process of training students on issues related to crystallography, by working on two graduate courses in Chemistry the University of Costa Rica. c) Participation as tutor thesis and graduation projects associated with investigation project. d) Collaboration in presenting papers at national conferences. As an important conclusion about my participation in the project, it highlights the experience developed in the interpretation of some related to the synthesis and characterization of nanometer materials, mainly in the X-ray diffraction and electrical characterization of materials scale phenomena. With regard specifically to the research results, a gap in which, for the first time, the company Intel strengthened the training of a generation of professionals in our country, where research forms a major part of their started skills.
Proyecto de Investigación. Instituto Tecnológico de Costa Rica. Escuela de Física; Escuela de Ciencia e Ingeniería de los Materiales; Universidad de Costa Rica. Escuela de Química; Laboratorio Nacional de Nanotecnología LANOTEC-CENAT, 2011
Keywords: Nanomateriales; Caracterización; Mediciones; Calibración; Moléculas